2022
DOI: 10.3389/frai.2022.842546
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Phonetic Space of Prosodic Focus Marking

Abstract: Focus is known to be expressed by a wide range of phonetic cues but only a few studies have explicitly compared different phonetic variables within the same experiment. Therefore, we presented results from an analysis of 19 phonetic variables conducted on a data set of the German language that comprises the opposition of unaccented (background) vs. accented (in focus), as well as different focus types with the nuclear accent on the same syllable (broad, narrow, and contrastive focus). The phonetic variables ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…In categorical intonation analyses using transcription systems related to ToBI (Silverman et al, 1992;Beckman et al, 2005; see also other chapters in Jun, 2005), these F0 differences are reflected in lower proportions of downstepped H* accents (Baumann et al, 2007) and falling accents (Grice et al, 2017) in narrow focus compared to broad focus. Similar differences in the nuclear-accented word have also been attested between narrow and corrective focus: Compared to narrow focus, corrective focus is characterized by longer durations (Kügler, 2008), higher intensities (Breen et al, 2010), as well as larger F0 excursions, and higher F0 peaks with later temporal alignment (Baumann et al, 2006;Grice et al, 2017;Roessig et al, 2022).…”
Section: Focus and (The Nuclear) Accentmentioning
confidence: 78%
See 2 more Smart Citations
“…In categorical intonation analyses using transcription systems related to ToBI (Silverman et al, 1992;Beckman et al, 2005; see also other chapters in Jun, 2005), these F0 differences are reflected in lower proportions of downstepped H* accents (Baumann et al, 2007) and falling accents (Grice et al, 2017) in narrow focus compared to broad focus. Similar differences in the nuclear-accented word have also been attested between narrow and corrective focus: Compared to narrow focus, corrective focus is characterized by longer durations (Kügler, 2008), higher intensities (Breen et al, 2010), as well as larger F0 excursions, and higher F0 peaks with later temporal alignment (Baumann et al, 2006;Grice et al, 2017;Roessig et al, 2022).…”
Section: Focus and (The Nuclear) Accentmentioning
confidence: 78%
“…It has been shown that nuclear-accented words are realized with different prosodic patterns depending on the focus condition. In particular, nuclear-accented words in narrow focus are longer than their counterparts occurring in broad focus (e.g., Baumann et al, 2006;Eady & Cooper, 1986;Kügler, 2008) and exhibit higher intensities (Breen et al, 2010; see also Roessig et al, 2022 although here the effect size of intensity was rather small). Additionally, higher F0 values, larger F0 excursions and later F0 peak alignments have been found for narrow focus compared to broad focus (Baumann et al, 2006;Breen et al, 2010;Eady & Cooper, 1986;Féry & Kügler, 2008;Grice et al, 2017;Roessig et al, 2022).…”
Section: Focus and (The Nuclear) Accentmentioning
confidence: 80%
See 1 more Smart Citation
“…Due to space constraints, we do not discuss here the findings for prosodic factors, except to note that they align with the prior literature: creak is significantly more likely in syllables that are unaccented (Roessig, Winter, & Mücke, 2022:4), onsetless IP-initially (Dilley et al, 1996:423; Garellek, 2014:106), IP-final (Abdelli-Beruh et al, 2014:187; Podesva, 2013:431), and in IPs ending in a low-falling (L-L%) or low-rising (L-H%) tone (Redi & Shattuck-Hufnagel, 2001:426). The full best-fit model is presented in the Appendix.…”
Section: Resultsmentioning
confidence: 77%
“…Speakers produced sentences, such as "Die Oma hat der Mila gewunken" (The grandma waved at Mila.). The focused element of the analysis was the first syllable from each of the ten girl names (Table S1), which were produced in three different focus conditions that reflect different degrees of prominence, ranging from low to high prominence on the name 15,16 . Tongue body movements refer to the production of the vowels (i, e, a, o, u), tongue tip movements to the production of the alveolar consonant /l/ and lower lip movements to the production of the labial consonant /m/.…”
Section: Methodsmentioning
confidence: 99%